The gardens of desire : Marcel Proust and the fugitive sublime - Brown, Stephen Gilbert, 1949- (State University of New York Press, 2004)
Offers a psychocritical reading of Proust's À la recherche du temps perdu (Remembrance of Things Past).
Keywords: Proust, Marcel, -- 1871-1922 -- Criticism and interpretation.; Proust, Marcel, -- 1871-1922 -- Critique et interprétation.; Proust, Marcel, -- 1871-1922; Desire in literature.; Désir dans la littérature.; LITERARY CRITICISM -- European -- French.; Desire in literature; Criticism, interpretation, etc.